2007
DOI: 10.1021/jf0721186
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of a Proanthocyanidin-rich Extract from Longan (Dimocarpus longan Lour.) Flowers on Nitric Oxide Production in LPS-Stimulated Macrophage Cells

Abstract: Anthocyanidins found in certain flowers have been shown to act as strong antioxidants in various systems, exhibiting multiple biological actions. The antioxidative effects of water extract and ethanolic extract of longan (Dimocarpus longan Lour.) flowers were evaluated by radical scavenging activity and compared to those of gallic acid, myricetin, and epigallocatechin gallate. In this study, the suppressive effects of longan flower extracts on nitric oxide and prostaglandin E2 production were investigated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 41 publications
5
53
0
Order By: Relevance
“…Values not sharing the same letter were significantly different (p \ 0.05, Fisher's test) PGE 2 , and TNF-a, with oligomers poorly effective with respect to polymers that contributed almost entirely to the HPE activity. These data may be the reflection of the amounts of proanthocyanidins assayed and/or indicate a different ability of oligomers and polymers to affect the macrophage response, as observed in other researches [44,[46][47][48][49]. To further highlight the role of these components, PF was also found almost effective as the whole HPE in inhibiting phosphorylation, and then activation, of IjB-a.…”
Section: Discussionsupporting
confidence: 54%
“…Values not sharing the same letter were significantly different (p \ 0.05, Fisher's test) PGE 2 , and TNF-a, with oligomers poorly effective with respect to polymers that contributed almost entirely to the HPE activity. These data may be the reflection of the amounts of proanthocyanidins assayed and/or indicate a different ability of oligomers and polymers to affect the macrophage response, as observed in other researches [44,[46][47][48][49]. To further highlight the role of these components, PF was also found almost effective as the whole HPE in inhibiting phosphorylation, and then activation, of IjB-a.…”
Section: Discussionsupporting
confidence: 54%
“…We have demonstrated that the hot water reflux or ethanol extract of the longan flower, contained abundant proantocyanidins and rarely anthocyanins, suppresses nitric oxide and prostaglandin E2 production in lipopolysaccharide -stimulated macrophage cell line RAW264.7 and may be the potential source of natural dietary anti-oxidants and antiinflammatory agent [20] . The longan flower extract (LFE), analyzed by Professor Hwang and colleagues, exhibits a strong anti-oxidant activity, which is mainly due to (-)epicatechin and proanthocyanidin A2 [26] .…”
Section: Longan Flowers and Seeds In Tcmmentioning
confidence: 99%
“…Non-steroidal antiinflammatory drugs have been documented in animal and human studies to reduce the risk of colorectal cancer and adenomatous polyps and have been implicated as a cancer prevention and treatment strategy [1,[17][18][19] . Longan flowers and seeds have been analyzed and were found to possess rich amounts of polyphenols, including proanthocyanidin A2, (-)-epicatechin, gallic acid and ellagic acid, and exhibit strong antioxidant and inflammatory activities [20][21][22][23][24] . Recently, several studies by our research group have further revealed that longan flower and seed extracts exhibit an anti-cancer activity towards colorectal, liver, lung, cervical and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several Thai traditional plants such as ginger (Grzanna, Lindmark, & Frondoza, 2005), longan (Ho, Hwang, Shen, & Lin, 2007; Wang, Tang, Chiu, & Huang, 2012), and Gymnema inodorum (Shimizu et al., 2001) have been reported for their antioxidant and anti‐inflammatory activities. Thus, they have potential value in treating various diseases including diseases involving inflammation.…”
Section: Introductionmentioning
confidence: 99%